Uji Efektivitas Ekstrak Etanol Daun Ketapang (Terminalia cattapa L.) Terhadap Bakteri Patogen - Saputri, Muharni; Mierza, Vriezka; Zebua, Nilsya Febrika; Panjaitan, M Ridho Pangestu (Journal of Pharmaceutical and Health Research, 2024)
Antiba Antibacterials work by preventing and managing the growth of pathogenic bacteria. The goal of controlling bacterial growth is to stop the spread of infection. Basically, people use synthetic drugs in antibacterial prevention but often there is a lot of resistance in the human body that can cause adverse effects. The active ingredients in ketapang leaves have the potential to act as natural antibiotics and antibacterials to combat antibiotic resistance. To determine the antibacterial effectiveness of these chemical compounds against bacteria Pseudomonas aeruginosa, Demacoccus nishinomiyaensi, Stapylococcus epidermidis and Micrococcus luteus, a study was conducted with the aim of knowing the content of chemical compounds contained in ketapang leaves based on maceration results. This study uses an experimental descriptive method with Ketapang leaf test material (Terminalia cattapa L.) This research stage includes making simplisia, maceration extraction using ethanol solvent, antibacterial activity test agar well diffusion method and analysis of chemical compound components by phytochemical screening.The results of drying fresh ketapang leaves produce as much as 1.6 kg of simplisia, and when 300 grams of ketapang leaf simplisia is macerated using ethanol pro analysis, 1.5 kg of simplisia is obtained. The ethanol extract from the maceration of ketapang leaves has antibacterial activity as shown by the inhibition of Pseudomonas aeruginosa bacteria by 18.38 mm, Dermacoccus nishinomiyaensis bacteria by 23.05 mm, Staphylococcus epidermidis bacteria by 18.71 mm, and Micrococcus luteus bacteria by 20.71 mm. After screening the ethanol extract of ketapang leaves, triterpenoid components, anthraquinone glycosides, saponins, and tannins were found. Flavonoid compounds were also found.